Association between Semen Exposure and Incident Bacterial Vaginosis. (8th November 2011) - Gallo, Maria F.; Warner, Lee; King, Caroline C.; Sobel, Jack D.; Klein, Robert S.; Cu-Uvin, Susan; Rompalo, Anne M.; Jamieson, Denise J.
Abstract : Objective . To identify correlates of incident bacterial vaginosis (BV) diagnosed with Nugent scoring among high-risk women. Study Design . We conducted both cohort and case-crossover analyses, stratified by HIV infection status, based on 871 HIV-infected and 439 HIV-uninfected participants in the HIV Epidemiology Research Study, conducted in 4 US sites in 1993–2000. Results . BV incidence was 21% and 19% among HIV-infected and -uninfected women, respectively. Fewer correlates of BV were found with case-crossover than with cohort design. Reporting frequent coitus (regardless of consistency of condom use) was correlated with BV in cohort analyses but not in case-crossover analyses. The sole correlate of BV in both types of analyses was the detection of spermatozoa on Gram stain, which is a marker of semen exposure. Conclusion . The inconsistent association between condom use and BV in prior studies could be from reporting bias. We found evidence of a relationship between semen exposure and incident BV.